Pemberian Senam Low Impact untuk Meningkatkan Kesehatan Reproduksi bagi Remaja Siswa-Siswi SMAN 7 Malang - Hilma Tsurayya Iftitahurroza; Anditri Weningtyas; Kiky Martha Ariesaka; Lintang Widya Sishartami; Arif Ladika; Faridatus Solikha; Fannia Yosa Bakhtiar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Adolescent reproductive health is a crucial aspect in the development of the quality of life for young generations. This community service activity aims to evaluate the effectiveness of low-impact exercise in improving reproductive health among students of SMAN 7 Malang. The method used is a participatory approach with low-impact exercise training conducted over 12 weeks. A total of 120 randomly selected students participated in this program. Reproductive health data were collected through questionnaires before and after the intervention, covering aspects such as knowledge of reproductive health, healthy living habits, and the frequency of reproductive health symptoms. Evaluation results showed a significant increase in participants' reproductive health scores after participating in the low-impact exercise program. The conclusion of this activity indicates that low-impact exercise can be an effective method in school reproductive health education programs. It is hoped that this program can be implemented routinely and become part of the physical education curriculum to improve adolescent reproductive health.